PENGARUH FAKTOR MOTIVASI PADA KEPUASAN KERJA KARYAWAN: STUDI KASUS YAYASAN PERGURUAN KRISTEN PETRA KEDIRI - Witanto, Felicia Dewi (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Personnel or human resources in education should be seriously follow the latest innovations and properly carried out its responsibility for the plan that had been in the apartment earlier or the vision and mission of an organization can be achieved. In this case the motivational factors play an important role improving employee satisfaction. Can improve employee performance and the satisfaction of employees in the performance, which is affected in terms of the individuals to be more responsible employees or the so called intrinsic factor and external aspects that support the performance of the employee in his work to create a better atmosphere in doing their jobs or the known as extrinsic factors. This study aims to determine the effect of factors on Job Satisfaction Employee Motivation Case Study Petra Christian College Foundation, Kediri. The population in this study were all employees or both men and women who work in Petra Christian Foundation Kediri .. The sampling technique used was non probability sampling with purposive sampling. Testing the hypothesis in this study, the authors used multiple linear regression analysis. The results of this study found that the influence of intrinsic motivation on job satisfaction and Extrinsic Motivation impact on Job Satisfaction